DETERMINANT FACTORS FOR UNIVERSITY STUDENT DROPOUT: A STUDY WITH NEW STUDENTS OF ACCOUNTING SCIENCES COURSES AT FEDERAL UNIVERSITIES IN THE NORTHEAST REGION - Sampaio, Sulanny de Souza; da Rocha, Maria Marcela Ramos; Cavalcante, Sueli Maria de Araújo; Rodrigues, Maxweel Veras (Advances in Scientific and Applied Accounting, 2020)
Objectives: To identify the determinant factors for student dropout in Accounting Sciences courses at Federal Universities in the Northeast region. Methods: This is a descriptive-exploratory study with a quantitative approach and survey usage. The sampling is non-probabilistic and intentional, covering all federal universities in the Northeast region of Brazil and consisting of 220 students who had enrolled in Accounting Science Courses in 2019. A questionnaire adapted from Cunha, Nascimento and Durso (2016) was also used, and data were interpreted through descriptive and factor analysis. Results or discussion: The results showed us that the vocational factor with the greatest factor loading was the one related to the type of admission, resulting from a successful selection process for the course in question and not for the student's preferred course. The most relevant institutional factor was related to the lack of information about the course as provided by the institution. The students' perception of the performance factor showed that the item with the highest factor loading was the one related to the student's difficulty in following the course because he or she did not have enough time to study. Contributions: The results indicate that the institution, with the information provided, may act directly upon the identified weaknesses through specific actions in order to reduce dropout rates.